2019
DOI: 10.1016/j.optlastec.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon direct laser writing of beam expansion tapers on single-mode optical fibers

Abstract: Small misalignments between two standard telecom single-mode fibers in a physical contact connection can lead to large optical losses. It is known that by expanding the mode field diameter of the fiber, the misalignment tolerances can be relaxed. One of the approaches to obtain this beam expansion is to use tapers. We propose an air-clad taper structure to transmit the fundamental mode of a single-mode fiber adiabatically to a 3 times larger mode field area in physical contact expanded beam connectors. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Meanwhile, the lenses for fiber-fiber coupling have also been studied. Figure 1F shows a beam expansion taper for SMF-SMF coupling by transmitting the fundamental mode adiabatically from a SMF to 3 times larger mode field area in physical contact expanded beam connectors (Vanmol et al, 2019). The trade-off between achievable insertion loss and misalignment tolerance relaxation was demonstrated by measuring a total insertion loss as low as 0.76 dB.…”
Section: Micro-opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the lenses for fiber-fiber coupling have also been studied. Figure 1F shows a beam expansion taper for SMF-SMF coupling by transmitting the fundamental mode adiabatically from a SMF to 3 times larger mode field area in physical contact expanded beam connectors (Vanmol et al, 2019). The trade-off between achievable insertion loss and misalignment tolerance relaxation was demonstrated by measuring a total insertion loss as low as 0.76 dB.…”
Section: Micro-opticsmentioning
confidence: 99%
“…(E) Microlens array printed on the top of single-mode and multi-core fiber for free-space light coupling (Dietrich et al, 2017). (F) Beam expansion taper for SMF-SMF coupling (Vanmol et al, 2019). multiplexer for OAM fiber communication.…”
Section: Micro-opticsmentioning
confidence: 99%
“…All previous considerations can be applied to these components as well. Moreover, it is possible to scale up the fabrication process and print taper structures on multi-fiber array glass blocks to increase the fiber count and density [29].…”
Section: Taper Fabrication and Characterizationmentioning
confidence: 99%
“…This fabrication technology allows the creation of 3D structures with full design freedom and submicrometer resolution [24]. The technique has already been used in the development of a microstructured antireflective coating [25], phase masks [26], lenses [27], [28] and mode-field expansion up-taper structures [29] on optical fiber tips. In the latter, we demonstrated the fabrication method for use in physical contact expanded beam fiber-to-fiber connections to relax the alignment tolerances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 3D nanoprinting technology, based on two-photon polymerization, is driving advancements in photonic miniaturization and integration. Research in this topic has shown that optical fibers can be functionalized for many applications, where the 2PP additive manufacturing technique has already been used in the development of a microstructured antireflective coating 8 , phase masks 9 , lenses 10,11 and mode-field expansion up-taper structures 12 on optical fiber tips. In the latter, we demonstrated the fabrication method for use in alignment tolerant physical contact expanded beam fiber-to-fiber connections.…”
Section: Introductionmentioning
confidence: 99%